Kandinsky and Synesthesia: A Cognitive and Cultural Complication of the Path to the Artist's Abstract Paintings of 1913. - Sibila, Helen M. (Tufts Archival Research Center, 2018)
Although Wassily Kandinsky often receives the title of "First Abstract Artist," he struggled to make non-objective works for many years. I believe that synesthesia frustrated, rather than facilitated, this process. Because of cognitive consequences of the condition, as well as interactions with the cultural environment, synesthesia made it difficult for Kandinsky to break away from the objects in his paintings until 1913.